Procedimiento para realizar la evaluación técnica en la etapa de formulación de un proyecto - Guatibonza Cárdenas, Alexander (Universidad de San Buenaventura - Cali, 2017)
This research is part of the project << implementation of techniques of management in the areas of projects management in organizations >> of Professor Ronald Rojas Alvarado of the Specialization in Integral Project Management of Projects of the Industrial Engineering Program of the University of San Buenaventura Cali. The purpose of this research is to identify the models, variables and covariates necessary to perform the technical evaluation of a project; this analysis has shown the presence of four basic components that are location, size, engineering and legal aspects required for the formulation of a project. The purpose of this paper is to present a procedure that allows executing this evaluation, based on information collected or provided and is consistent with the models and techniques commonly accepted. The methodology used was a descriptive quantitative approach with a transverse non-experimental design; information collection was performed via the generation of a database on digital and physical environment; the information was obtained by physical documents and consultations on Internet pages.